A simple and easy-to-prepare imidazole-based probe for the selective chromo-fluorogenic recognition of biothiols and Cu(II) in aqueous environments - Okda, Hazem Essam (2019)
A new simple and easy-to-prepare imidazole-based probe 1 was synthesized and used to detect Cu(II) and biothiols (Cys, Hcy and GSH) in aqueous environments. Addition of increasing amounts of Cu(II) to water (pH 7.4)-acetonitrile 90:10 v/v solutions of probe 1 induced the apperance of a red-shifted absorption together with a marked colour change from colorless to deep blue. In addition, probe 1 was fluorescent and a marked emission quenching in the presence of Cu(II) was observed. The optical response is selective and other cations tested do not induce significant chromo-fluorogenic modulations. Limits of detection for Cu(II) of 0.7 and 3.2 μM using UV–visible and fluorescence data were determined. On the other hand, addition of Cys, Hcy and GSH to the deep-blue water (pH 7.4)-acetonitrile 90:10 v/v solutions of the 1-Cu(II) complex reulted in a marked bleaching together with the appearance of a highly emissive band centred at 475 nm. Other amino acids tested induced negligible response. The limits of detection for Cys, Hcy and GSH using 1-Cu(II) and emission data are 6.5, 5.0 and 10.2 μM, respectively. These optical changes were ascribed to a biothiol-induced demetallation process of the 1-Cu(II) complex that released the free probe. Besides, probe 1 is non-toxic and can be used for Cu(II) detection in HeLa cells.